Step * 2 1 of Lemma Riemann-sum-rleq


1. : ℝ
2. : ℝ
3. a ≤ b
4. [a, b] ⟶ℝ
5. [a, b] ⟶ℝ
6. : ℕ+
7. ∀x:ℝ((x ∈ [a, b])  ((f x) ≤ (g x)))
8. icompact([a, b])
9. full-partition([a, b];uniform-partition([a, b];k)) ∈ {x:ℝ(a ≤ x) ∧ (x ≤ b)}  List
10. {x:ℝ(a ≤ x) ∧ (x ≤ b)}  List@i
11. full-partition([a, b];uniform-partition([a, b];k)) v ∈ ({x:ℝ(a ≤ x) ∧ (x ≤ b)}  List)@i
12. : ℤ@i
13. 0 ≤ i@i
14. i ≤ (||v|| 2)@i
⊢ ((f v[i]) (v[i 1] v[i])) ≤ ((g v[i]) (v[i 1] v[i]))
BY
Assert ⌜(f v[i]) ≤ (g v[i])⌝⋅ }

1
.....assertion..... 
1. : ℝ
2. : ℝ
3. a ≤ b
4. [a, b] ⟶ℝ
5. [a, b] ⟶ℝ
6. : ℕ+
7. ∀x:ℝ((x ∈ [a, b])  ((f x) ≤ (g x)))
8. icompact([a, b])
9. full-partition([a, b];uniform-partition([a, b];k)) ∈ {x:ℝ(a ≤ x) ∧ (x ≤ b)}  List
10. {x:ℝ(a ≤ x) ∧ (x ≤ b)}  List@i
11. full-partition([a, b];uniform-partition([a, b];k)) v ∈ ({x:ℝ(a ≤ x) ∧ (x ≤ b)}  List)@i
12. : ℤ@i
13. 0 ≤ i@i
14. i ≤ (||v|| 2)@i
⊢ (f v[i]) ≤ (g v[i])

2
1. : ℝ
2. : ℝ
3. a ≤ b
4. [a, b] ⟶ℝ
5. [a, b] ⟶ℝ
6. : ℕ+
7. ∀x:ℝ((x ∈ [a, b])  ((f x) ≤ (g x)))
8. icompact([a, b])
9. full-partition([a, b];uniform-partition([a, b];k)) ∈ {x:ℝ(a ≤ x) ∧ (x ≤ b)}  List
10. {x:ℝ(a ≤ x) ∧ (x ≤ b)}  List@i
11. full-partition([a, b];uniform-partition([a, b];k)) v ∈ ({x:ℝ(a ≤ x) ∧ (x ≤ b)}  List)@i
12. : ℤ@i
13. 0 ≤ i@i
14. i ≤ (||v|| 2)@i
15. (f v[i]) ≤ (g v[i])
⊢ ((f v[i]) (v[i 1] v[i])) ≤ ((g v[i]) (v[i 1] v[i]))


Latex:


Latex:

1.  a  :  \mBbbR{}
2.  b  :  \mBbbR{}
3.  a  \mleq{}  b
4.  f  :  [a,  b]  {}\mrightarrow{}\mBbbR{}
5.  g  :  [a,  b]  {}\mrightarrow{}\mBbbR{}
6.  k  :  \mBbbN{}\msupplus{}
7.  \mforall{}x:\mBbbR{}.  ((x  \mmember{}  [a,  b])  {}\mRightarrow{}  ((f  x)  \mleq{}  (g  x)))
8.  icompact([a,  b])
9.  full-partition([a,  b];uniform-partition([a,  b];k))  \mmember{}  \{x:\mBbbR{}|  (a  \mleq{}  x)  \mwedge{}  (x  \mleq{}  b)\}    List
10.  v  :  \{x:\mBbbR{}|  (a  \mleq{}  x)  \mwedge{}  (x  \mleq{}  b)\}    List@i
11.  full-partition([a,  b];uniform-partition([a,  b];k))  =  v@i
12.  i  :  \mBbbZ{}@i
13.  0  \mleq{}  i@i
14.  i  \mleq{}  (||v||  -  2)@i
\mvdash{}  ((f  v[i])  *  (v[i  +  1]  -  v[i]))  \mleq{}  ((g  v[i])  *  (v[i  +  1]  -  v[i]))


By


Latex:
Assert  \mkleeneopen{}(f  v[i])  \mleq{}  (g  v[i])\mkleeneclose{}\mcdot{}




Home Index